A comparative study on correlation between personal background and interior color preference. Issue 4 (11th July 2014) - Baniani, Mahshid; Yamamoto, Sari
Abstract In this research, we identify and investigate some of the factors influencing residential color preference. We have taken social environment as a primary focus and the influence of a person's residential, regional, educational, and personal background have been examined. A questionnaire, two drawings (one of a bedroom and another of the exterior of a few houses) and 24 color pencils were prepared. In total, 319 data were gathered from Japanese students living in Japan, Foreign students living in Japan, and Iranian students living in Iran, with 301 applicable data. One of the questions was the respondent's favorite color. The results showed that more than 96.7% have used their favorite colors in the drawings. Blue hues were used most by people living in coastal areas (P < 0.05). Education had a strong correlation with number of color varieties (P < 0.01). Moreover, students who had parents with art backgrounds had used more colors in the drawings rather than the ones with parents with no art background (P < 0.05). Foreigners and Iranians have used more color varieties compared to Japanese (P < 0.05). Ultimately, it was observed that among the case studies (regional, residential, and educational), education had a strong positive correlation with number of color varieties (P < 0.01). © 2014 Wiley Periodicals, Inc. Col Res Appl, 40, 416–424, 2015